A case–control study of risk factors associated with Zoon balanitis in men. (3rd April 2019) - Piaserico, S.; Orlando, G.; Linder, M.D.; Cappozzo, P.; Zarian, H.; Iafrate, M.
Abstract: Background: Zoon balanitis (ZB) is a chronic inflammatory benign mucositis. Its etiopathogenesis still remains hypothetical and speculative. Objectives: To determine risk factors associated with genital ZB in men. Methods: This is a case–control study including 30 patients diagnosed with ZB and 54 patients with dermatological diseases other than ZB enrolled in the Dermatological Clinic of the University of Padova, Italy, from September 2015 to June 2018. Univariate and multivariate logistic regression analyses were used for analysis of data collected. Results: According to multivariate logistic regression analysis, risk factors for ZB were as follows: the mean daily cigarettes consumption (OR 1.065; 95% CI 1.8‐11.4; P = 0.006) and the number of weekly foreskin retractions (OR 0.847; 95% CI 5.5–24.1; P = 0.003). There were no statistically significant differences between cases and controls according to age, presence of circumcision as well in number of sexual partners. Conclusions: To our knowledge, this is the first case–control study showing that smoking and poor genital hygiene are associated with being affected by ZB.